SISTEM INFORMASI LABORATORIUM BERBASIS WEBSITE DI PROGRAM STUDI D IV TEKNIK INFORMATIKA POLITEKNIK HARAPAN BERSAMA TEGAL - Nishom, M.; Wibowo, Dega Surono (Vocational School Diponegoro University, 2020)
Laboratory is one of the important components in a college, where scientific research, experimentation, development or scientific training activities and even teaching-learning activities are carried out in it, so that a good schedule of space usage management and information on the availability of equipment is needed to support the smooth operation of laboratory use. At present, the process of laboratory services in the Informatics Engineering department of Politeknik Harapan Bersama is still carried out in a conventional manner, where all spatial use activities are recorded in a book, making it ineffective and less efficient. This study aims to build a Laboratory Information System in the Informatics Engineering Department of Politeknik Harapan Bersama. Data collection was performed using the triangulation method. StarUML was chosen as a tool for modeling UML-based systems, and blackbox as a method for testing system functionality. The results of this study are Web-based Laboratory Information Systems. It is expected that with this information system, it can further improve the service and effectiveness of the use of laboratories in the Informatics Engineering Department.